Incidence of Haemophilus influenzae type b among children less than 5 years and resistance to antibiotics in Iraq. - Almelan, Maha F. (Journal of the Faculty of Medicine Baghdad, 2015)
Back ground: Meningitis is an inflammation of the protective membranes covering the brain and spinal cord that known as meninges. It is the major cause of morbidity and mortality among infants and children less than the age of 5 years. Objectives: To determine Haemophilus influenzae type b meningitis incidence in children aged less than 5 years and choice a drug for treatment Patients and methods: During period from Febraury 2012 to first March 2013 ,250 Cerebrospinal fluid (CSF) specimens were collected from children less than 5 years ,which clinically diagnosed with meningitis ,in several hospitals of Iraq.Microbiological, biochemical, latex agglutination test and antibiotics sensitivity were used to identify and choice the antibiotic that should be used for treatment Results: Culturing CSF specimens identified 18 confirmed cases of Haemophilus influenzae type b meningitis among 250 CSF specimens depending on biochemical and serotyping. The incidence of Haemophilus influenzae type b meningitis among infants less one years of age was 12(66.6%) compared to 6(33.3%) for older children . Incidence among males was 11(61.1%) compared to 7(38.8%) for females. Haemophilus influenzae type b meningitis is sensitive to Ampencillin , Ciprofloxacin, Cefotaxime, Cefotriaxone, Chloramphenicol, while resistant to Trimetheprim-sulfamethoxazole and Gentomycin. Conclusions: Haemophilus influenzae type b meningitis was most common in children less than 1 years.